High-throughput profiling and analysis of antibiotic resistance genes in East Tiaoxi River, China. (November 2017) - Zheng, Ji; Gao, Ruixia; Wei, Yuanyuan; Chen, Tao; Fan, Jiqing; Zhou, Zhenchao; Makimilua, Tiimub Benjamin; Jiao, Yanan; Chen, Hong
Abstract: The rapid human activities and urbanization exacerbate the human health risks induced by antibiotic resistance genes (ARGs). In this study, the profiling of ARGs was investigated using high-throughput qPCR from water samples of 13 catchment areas in East Tiaoxi River, China. High prevalence of ARGs indicated significant antibiotic resistance pollution in the research area (absolute abundance: 6.1 × 10 8 –2.1 × 10 10 copies/L; relative abundance: 0.033–0.158 copies/cell). Conventional water qualities (COD, TN, TP, NH3 -N), bacterial communities and mobile gene elements (MGEs) were detected and analyzed as factors of ARGs shift. Nutrient and MGEs showed positive correlation with most ARGs ( P < 0.05) and bacteria community was identified as the key contributing factor driving ARGs alteration. With the land-use study and field investigation, country area, especially arable, was expected as a high spot for ARGs shift and pathogen breeding. Comparing to environmental background, promotion of ARGs and marked shift of bacterial community were observed in country and urban city areas, indicating that human activities may lead to the spread of ARGs. Analysis of factors affecting ARGs in this study may shed new light on the mechanism of the maintenance and propagation of ARGs in urban rivers. Graphical abstract: Highlights: High prevalence of antibiotic resistance genes was influenced by human activities. Bacteria community was the key contributing factor driving ARGs alteration. Nutrient and mobile gene elements had positive correlation with most ARGs ( P < 0.05). Country area was a high spot for antibiotic resistome shift and pathogen breeding.